The role of neoadjuvant hormonotherapy in patients with locally advanced breast cancer - is that a chance for agents of new generation? - Wełnicka-Jaśkiewicz, Marzena; Rogowski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2002)
The management of locally advanced breast cancer (LABC) has changed considerably during this century. Based on the work of Halsted, radical mastectomy was established as the principal standard treatment for breast cancer at the turn of the 20th century. Subsequent reports have consistently demonstrated poor results of radical mastectomy in LABC patients. In consequence, radiation therapy used as a sole modality or as an adjunct to surgery assumed a more prominent role in the management of these patients. More recently, a systemic therapy as an adjunct to locoregional modalities became the standard of care in the majority of LABC patients. Currently most patients with LABC are treated with primary chemotherapy or, especially in elderly patients, with hormonal agents. Tamoxifen has been the treatment of choice in that group of patients until selective aromatase inhibitors were introduced. These compounds were found to be more active than tamoxifen in metastaic breast cancer and in LABC. Most recently, a remarkable activity of novel class of agents, selective estrogen receptor modulators (SERM) has been demonstrated. The aim of this paper is to review the role of primary hormonotherapy in LABC patients with the potential, focus on recently introduced hormonal agents.